Some historical aspects of special (protective) combat uniform - Orel, О. V. (Honor and Law, 2019)
Some causes to design a special (protective) combat uniform. Its use and reasons of its changes are being highlighted. The accent is laid on the problems which arise at the modern stage of state development.